Counterterrorism - Does It Work? - Eric van Um; Daniela Pisoiu (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
The terrorist threat has increased in importance over the last decade and Western governments have implemented a multitude of measures to address it. Their numbers and the significant financial cost they involve have, however, not been matched with an adequate evaluation of effectiveness. We can therefore only make limited statements on whether or not counterterrorism policy has been effective. Three conclusions with policy implications can nevertheless be drawn from our analysis: the dependency on the local context; the ineffectiveness of measures entailing the use of force; and the need for more evaluation research on protective measures.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330